Identification and management of Bipolaris sorokiniana in wheat and barley in Southeast Kazakhstan - A. Kharipzhanova; Y. Dutbayev; G. Erginbas-Orakci; A. A. Dababat; Ş. G. Korkulu; S. Aydın; T. Paulitz; G. Özer; T. Bozoğlu; S. Zholdoshbekova; N. Sultanova; A. Kokhmetova (Brazilian Journal of Biology)
Abstract Wheat and barley serve as significant nutrient-rich staples that are extensively grown on a global scale, spanning over 219 million hectares. The annual combined global yield is 760.9 million tons, with Kazakhstan contributing 14.3 million tons of wheat and 3.83 million tons of barley to this total. The productivity of grain crops has declined annually due to fungal disease, especially root and crown rot caused by Bipolaris sorokiniana and Fusarium spp. Research has focused on pinpointing the pathogens responsible for common root rot in various types of wheat and barley grown in Southeast Kazakhstan. The main goal was to examine the efficacy of certain chemical and biological substances in safeguarding barley seedlings during the early growth stage against root rot root rot. Moreover, this study sought to gauge their effects on seed quality by examining aspects such as germination rates, the colonization of seeds by particular fungal pathogens, and the overall vitality of seeds and seedlings. Visual inspection of the plants revealed that the prevalence of B. sorokiniana was an average of 51.8%, and that of Fusarium species was 58.6%. Three isolates were obtained from the roots of the winter wheat promising line 231, three from the spring wheat roots of the Kazakh variety 10, four from the winter wheat variety Steklovidnaya variety 24, fourteen from the spring barley variety Symbat, and fourteen from the winter barley variety Aidyn variety 2. The external spread of common root rot on spring wheat and spring barley varieties reached 50% and 53%, respectively. Promising line 231 of winter wheat and variety Kazakh 10 of spring barley were affected by the disease by 60%, whereas the winter wheat Steklovidnaya 24 was impacted by 67%. Molecular analysis of B. sorokiniana isolates via species-specific primers (COSA_F/COSA_R) from infected plant tissues confirmed their identification. Koch postulates were fulfilled for B. sorokiniana isolates Kz 48, 60, and 82 on Steklovidnaya 24 winter wheat and Symbat spring barley varieties. Biological products such as Phytosporin-M and Sporobacterin-Rassada significantly reduced the level of fungal infection, confirming their potential as environmentally safe plant protection agents.